Napoleon’s Panoptic Surveillance in George Orwell’s Animal Farm - Hayati, Indy Nur; Sukarini, Ni Wayan; Antari, Ni Made Suwari (Udayana University, 2025)
This article aims at examining the Panopticism within the novella Animal Farm during Napoleon’s leadership. This is done by applying the theory of Panopticism developed by Foucault as derived from Bentham's Panopticon model. This research utilizes the qualitative method and uses George Orwell’s novella Animal Farm (1945) as the data source. Foucault's panoptic schema is characterized by the impression of continuous observation internalized into self-surveillance. The findings suggest that the Animal Farm is considered a panoptic society, with the pigs corresponding to the tower inspectors and the farm animals as the prisoners. The panoptic surveillance comes in various forms and primarily through discourse, to influence the animals to conform to the norm of staying docile and accepting Napoleon’s leadership. The Panopticism in Animal Farm shows how discourse can be a powerful device of social control as a surveillance method, especially when it incites fear and the desire for security.